If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5 + 2x = -23 Solving -5 + 2x = -23 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 2x = -23 + 5 Combine like terms: -5 + 5 = 0 0 + 2x = -23 + 5 2x = -23 + 5 Combine like terms: -23 + 5 = -18 2x = -18 Divide each side by '2'. x = -9 Simplifying x = -9
| 3+4(2n-1)=55 | | 35.37+.20m=90 | | 12m-13=m+26 | | X-45(57)=69 | | 6n+2(2n-3)=-13 | | 5y=3y+4 | | 6x+2(3-x)=7x | | 42=2.8x | | 3x-4x-2+12x=18-6*2+4 | | -3x-5(5-3x)=8+15 | | 2x(3+x)=1 | | 42=2.8 | | (2x+32)=(x-8) | | 3x+9+x=37 | | 6x-28=x+32 | | 3p+3.5=38 | | e^3x-5*e^2x=135 | | (19b-7)-9(2b+2)=-7 | | 3x-2(2x+1)=8+4x | | 4b=908 | | 0.25m+3=4 | | 3-23=3x-8-2x | | -3-5x=-3 | | 2p^2+11p+9=0 | | 3x^2+6x=-15 | | y=2x^2+10x+12 | | 39=c-21 | | f(x)=5-8x | | 65=7x-2x+5 | | y=2x^2+20x+45 | | 2x=x+37 | | 4x-4=2x+50 |